2000
DOI: 10.1021/bi0002479
|View full text |Cite
|
Sign up to set email alerts
|

Metal Binding Modes of Alzheimer's Amyloid β-Peptide in Insoluble Aggregates and Soluble Complexes

Abstract: Aggregation of the amyloid beta-peptide (Abeta) into insoluble fibrils is a key pathological event in Alzheimer's disease. Zn(II) induces the Abeta aggregation at acidic-to-neutral pH, while Cu(II) is an effective inducer only at mildly acidic pH. We have examined Zn(II) and Cu(II) binding modes of Abeta and their pH dependence by Raman spectroscopy. The Raman spectra clearly demonstrate that three histidine residues in the N-terminal hydrophilic region provide primary metal binding sites and the solubility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
527
3
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(584 citation statements)
references
References 34 publications
49
527
3
4
Order By: Relevance
“…Comparison of the IR spectra of MeIm with those of MeIm in solutions containing Cu 2ϩ or Zn 2ϩ at MeIm/metal ratios of 4 ( Fig. 3, B-D) showed that the formation of Cu-4(5)MeImH and Zn-4(5)MeImH complexes induced an upshift of the (C 4 C 5 ) mode of methylimidazole, in total agreement with that reported with Raman spectroscopy (28,(77)(78)(79). Thus, the IR bands at 1605 cm Ϫ1 in Fig.…”
Section: Effect Of Cuzn-sod Reduction On Backbone and Active Sitesupporting
confidence: 87%
See 1 more Smart Citation
“…Comparison of the IR spectra of MeIm with those of MeIm in solutions containing Cu 2ϩ or Zn 2ϩ at MeIm/metal ratios of 4 ( Fig. 3, B-D) showed that the formation of Cu-4(5)MeImH and Zn-4(5)MeImH complexes induced an upshift of the (C 4 C 5 ) mode of methylimidazole, in total agreement with that reported with Raman spectroscopy (28,(77)(78)(79). Thus, the IR bands at 1605 cm Ϫ1 in Fig.…”
Section: Effect Of Cuzn-sod Reduction On Backbone and Active Sitesupporting
confidence: 87%
“…This was precisely described on His-Cu and His-Zn models of known structure, as well as on peptides modeling the copper-binding site of the prion protein, or the zinc/ copper-binding site of amyloid ␤-peptides (28,(77)(78)(79). The (C 4 C 5 ) mode occurs at 1590 -1580 cm Ϫ1 for histidine coordinated with N to copper or zinc (Scheme 2d) and at higher frequency, 1606 -1594 cm Ϫ1 , for histidine coordinated with N (28, 77-79) (Scheme 2 and Table I).…”
Section: Ir Markers Of Imidazole-metal Interactionsmentioning
confidence: 99%
“…We now extend the use of metal ions as probes of amyloid side chain packing in simple segments of the Aβ peptide of Alzheimer's disease. By restricting the possible metal binding sites, we show that Zn 2+ can specifically control the rate of self-assembly and dramatically regulate amyloid morphology via distinct coordination environments.The histidine dyad, His13 and His14, of Aβ is implicated in metal binding 8,9 and the metalmediated toxicity of Aβ. [10][11][12][13] In a parallel, in-register β-sheet arrangement with sheet Hbonds oriented along the fibril axis (Figure 1a.), 3,4 the side chains of the His13 and His14 are spaced 5 Å apart along each surface of the β-sheets (Figure 1b).…”
mentioning
confidence: 99%
“…The interaction between copper and Ab induces its aggregation in vitro (11) and favours Ab amyloid deposition in vivo, co-localizing in senile plaques; in fact, copper, iron and zinc levels increase in plaques up to 0.4 mM copper and up to 1 mM iron and zinc (12). Treatment with a copper-zinc chelator markedly and rapidly inhibits amyloid deposition in the brain of Alzheimer's disease transgenic mice (13).…”
Section: The Pathological Role Of Copper In Alzheimer's Diseasementioning
confidence: 99%